2016
DOI: 10.1093/jxb/erw147
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics reveals the importance of nitrogen source to control glucosinolate metabolism inArabidopsis thalianaandBrassica oleracea

Abstract: HighlightA quantitative proteomic approach demonstrates how ammonium nutrition induces glucosinolate biosynthetic and catabolic pathways in Arabidopsis and broccoli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 58 publications
5
42
2
Order By: Relevance
“…On the other hand, the activation of GLS and GSH synthesis could also be part of the plant strategy to store N when cell NH 4 + availability is excessive. These results obtained in oilseed rape are in line with those reported in a recent study from our research group where we showed an increase in the synthesis of aliphatic and indolic GLS in shoots of A. thaliana and broccoli under mild ammonium stress [ 27 ]. Similarly, Zaghdoud et al (2016) [ 26 ] also observed higher levels of indolic GLS in broccoli plants under high ammonium stress associated to Trp accumulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the activation of GLS and GSH synthesis could also be part of the plant strategy to store N when cell NH 4 + availability is excessive. These results obtained in oilseed rape are in line with those reported in a recent study from our research group where we showed an increase in the synthesis of aliphatic and indolic GLS in shoots of A. thaliana and broccoli under mild ammonium stress [ 27 ]. Similarly, Zaghdoud et al (2016) [ 26 ] also observed higher levels of indolic GLS in broccoli plants under high ammonium stress associated to Trp accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies reported no differences or even reduced levels of GLS in plants cultured with NH 4 + as sole N source [ 23 , 24 ], while other showed increased GLS levels in response to NH 4 + availability [ 25 , 26 ]. Recently, we also reported the activation of GLS metabolism in leaves of A. thaliana and broccoli plants grown under ammonium nutrition suggesting N management as a way to control GLS metabolism [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supplying the two forms of nitrogen in a specific ratio will lead to the optimum growth; this finding has been reported in species such as apple (Malus domestica Borkh) [18,19], tomato (Solanum lycopersicum L.) [20,21], and rice (Oryza sativa L.) [22][23][24]. Predominant sources of ammonia N may also negatively affect the whole plant biomass deposition in some species, such as Arabidopsis thaliana [25,26]; while in another study, Arabidopsis plants displayed the potential of stimulating glucosinolate metabolism with ammonium nutrition [27]. An appropriate ammonium-nitrate ratio can enhance plant tolerance to abiotic stresses.…”
Section: Introductionmentioning
confidence: 65%
“…Tryptophan-derived indole-3-acetaldoxime in the indolic group—also known as a precursor for auxin related to plant growth and development—and camalexin biosynthesis controlling deter bacterial and fungal pathogens [ 34 , 35 ]. Recently, some aliphatic and indolic GSLs have been reported that are involved in primary metabolism in plants, such as nitrogen and sulfur sources, and abiotic stresses, such as salinity, light, and elevated CO 2 [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Metabolic and Regulatory Pathways Of Gsl Biosynthesismentioning
confidence: 99%